2018
DOI: 10.1155/2018/3050278
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Saudi Emergency Physicians toward t-PA Use in Stroke

Abstract: Background and Objectives Tissue plasminogen activator (t-PA) within 4.5 hours from onset improves outcome in patients with ischemic stroke and has been recommended by several international guidelines. Since its approval in 1996, the debate among emergency physicians continues particularly around the result interpretation of the first positive randomized controlled trial, the National Institute of Neurological Disorders and Stroke (NINDS) clinical trial. This lack of consensus might negatively affect the deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The self-administered questionnaire was developed based on the review of different literature included the following sections: 5,6,8 1. Descriptive data, including age, gender, level of education, job title, nationality, years of experience, and estimated number of stroke patients seen per week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-administered questionnaire was developed based on the review of different literature included the following sections: 5,6,8 1. Descriptive data, including age, gender, level of education, job title, nationality, years of experience, and estimated number of stroke patients seen per week.…”
Section: Methodsmentioning
confidence: 99%
“…4 A previous study conducted in Riyadh, Saudi Arabia, among emergency services personnel reported that there was a lack of knowledge of the cardinal stroke symptoms, and the uses and therapeutic time window of t-PA. 5 A recent study conducted in Riyadh, Saudi Arabia, among emergency physicians revealed a relatively low level of knowledge and the presence of negative attitudes toward t-PA use. 6 Thrombolytic programs have been implemented in many hospitals in Saudi Arabia, but the situation among hospitals in the Qassim region is currently suboptimal. Emergency and medicine physicians are the primary providers of acute stroke care in Qassim due to the current shortage of neurologists, with a total of only four neurologists in the three major hospitals in Qassim at the time of this study and the lack of stroke care organization and patient access to IV-t-PA.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency doctors' knowledge is necessarily broader and shallower in scope. They have less chance to be familiar with complex neuro‐physiological concepts compared to neurologists 29,30 . And without the concept of the penumbra, and its operational correlate of the 3‐hour therapeutic window, there would indeed be no grounds to distinguish between the NINDS trial and its related trials.…”
Section: Epistemic Evaluation In Acute‐stroke Decision‐makingmentioning
confidence: 99%
“…The physicians' fears of risk of intracranial hemorrhage among other side effects of thrombolytic therapy may play a role in clinical decision to treat patients which affects the DTN [37]. Khathami et al [38] claimed that the main reasons for emergency physicians who do not recommend tPA use were that they found the said treatment lacking efficacy or effectiveness. The lack of exposure, education and awareness about eligibility could be the contributory factors [39].…”
Section: Barriers On Timely Administration Of Tpamentioning
confidence: 99%